IMPLEMENTATION OF 5E LEARNING CYCLE MODEL ON PROCESS SCIENCE SKILLS PROSPECTIVE STUDENT TEACHER OF UNIVERSITY OF TANJUNGPURA - Rody Putra Sartika; Lukman Hadi (ICoTE Proceedings)
The main purpose of this study to determine whether there was significant difference of process science skills between student who were taught through learning 5E learning cycle and conventional model on colligative properties of solutions concept. Nonequivalent control group  design was adopted in this study as research design. Population consisted of all second semester students of chemistry education program according to purposive sampling technique, A1 and A2 class were chosen as experimental and control group. Process science skill test was used to collect data. According to independent t test, it was found that p-value = 0.017<a = 0.05, which meant if there was a significant difference of process science skill between students who were taught through 5E learning cycle and conventional model on colligative properties of solutions concept.